Labour migration flows: EU8+2 vs EU-15 - Josifidis, Kosta; Supic, Novica; Pucar, Emilija Beker (Journal of Business Economics and Management, 2014)
The aim of this paper is to determine whether, and to what extent, the migrations from the EU-8+2 to the EU-15 were motivated by differences in earnings and productivity and to what extent by differences in welfare state generosity during the period of the transitional arrangements. On these grounds, a distinction emerges between “favourable” and “unfavourable” migrations on one hand and immigration net winners and losers on the other hand. The obtained results represent an empirical ground for the discussion on the thesis according to which more generous welfare state regimes will be more susceptible to the influx of unfavourable immigrants during the upcoming period of the free movement of labour, while the less generous welfare state regimes will be a magnet for the favourable immigration influx within the EU-27.First published online: 02 Jan 2014